2021
DOI: 10.1038/s41598-021-83676-1
|View full text |Cite
|
Sign up to set email alerts
|

Modern dolomite formation caused by seasonal cycling of oxygenic phototrophs and anoxygenic phototrophs in a hypersaline sabkha

Abstract: The “Dolomite Problem” has been a controversy for over a century, owing to massive assemblages of low-temperature dolomite in ancient rocks with little dolomite forming today despite favorable geochemical conditions. Experiments show that microbes and their exopolymeric substances (EPS) nucleate dolomite. However, factors controlling ancient abundances of dolomite can still not be explained. To decode the enigma of ancient dolomite, we examined a modern dolomite forming environment, and found that a cyclic shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 76 publications
(105 reference statements)
1
23
0
Order By: Relevance
“…Mounting evidence confirms that dolomite is more common in modern evaporitic saline environments than it is in modern, open-marine sediments. In the past decades, dolomite has been frequently found in modern saline lakes ( Deckker and Last, 1988 ; Deng et al, 2010 ; Samylina and Zaytseva, 2019 ; Li et al, 2020 ), coastal evaporitic sabkhas ( Bontognali et al, 2010 ; Shalev et al, 2020 ; Diloreto et al, 2021 ), and saline soils ( Sherman et al, 1947 ; Kohut et al, 1995 ), while by contrast, almost no dolomite precipitation has been reported in the ocean ( Gregg et al, 2015 ). The concentrations of various ions in these evaporative saline systems are significantly higher than those in surface seawater, including Na + , Ca 2+ , Mg 2+ , Cl – , and ( Deng et al, 2010 ; Kolpakova et al, 2019 ), leading to the inference that dolomite precipitation may be linked to high salinity, high sulfate concentration, and increasing Mg/Ca molar ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence confirms that dolomite is more common in modern evaporitic saline environments than it is in modern, open-marine sediments. In the past decades, dolomite has been frequently found in modern saline lakes ( Deckker and Last, 1988 ; Deng et al, 2010 ; Samylina and Zaytseva, 2019 ; Li et al, 2020 ), coastal evaporitic sabkhas ( Bontognali et al, 2010 ; Shalev et al, 2020 ; Diloreto et al, 2021 ), and saline soils ( Sherman et al, 1947 ; Kohut et al, 1995 ), while by contrast, almost no dolomite precipitation has been reported in the ocean ( Gregg et al, 2015 ). The concentrations of various ions in these evaporative saline systems are significantly higher than those in surface seawater, including Na + , Ca 2+ , Mg 2+ , Cl – , and ( Deng et al, 2010 ; Kolpakova et al, 2019 ), leading to the inference that dolomite precipitation may be linked to high salinity, high sulfate concentration, and increasing Mg/Ca molar ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Saline environments are favorable for microbial formation of Mg-rich carbonates (Al Disi et al 2019 ). Indeed, environmental shifts from low- to high- salinity has been shown to increase the fraction of carboxylic groups on EPS, suggesting that such shifts could increase the Mg-consuming precipitation of dolomite (Diloreto et al 2021 ). At low pH, EPS from Bacillus megaterium shows a more dense and compact structure due to altered interactions of intermolecular hydrogen bonds (Wang et al 2012a ).…”
Section: Key Ingredients For Biomineralization In Porous and Fracture...mentioning
confidence: 99%
“…25 Sabkhas occur in regions characterized by extreme climatic and environmental conditions, such as high temperature, salinity, light intensity, etc. 26,27 Since long, sabkhas have been studied as modern analogues for interpreting some ancient dolomite-rich sedimentary sequences, and several models for dolomite formation are based on the study of these depositional settings. 28 More recent studies indicate that not only evaporation, but also microbial processes may play a key role in these evaporitic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have focused on the community composition of microbial mats (with top layers comprised mostly of cyanobacteria and anoxygenic phototrophs) that promote the formation of dolomite in a sabkha environment, revealing that anoxygenic phototrophic microbes are particularly important for the mineralization process. 10,27 Specically, a cyclic shi in microbial community between cyanobacteria and anoxygenic phototrophs results in the production of EPS with an increased concentration of carboxylic functional groups, which in turn favors dolomite formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation